Entheseal Involvement in Spondyloarthritis (SpA) and Gout: An Ultrasound Comparative Study - Ventura-Ríos, Lucio; Cazenave, Tomas; Hernández-Díaz, Cristina; Gallegos-Nava, Selma; Gómez-Ruiz, Citlallyc; Rosemffet, Marcos; Silva-Luna, Karina; Rodríguez-Henríquez, Pedro; Vázquez-Mellado, Janitzia; Casasola-Vargas, Julio; Cruz-Arenas, Esteban; de Miguel, Eugenio M. (Frontiers in Medicine, 2022)
Objective To compare the assessment of entheses in subjects with spondyloarthritis (SpA) with patients with gout by the Madrid Sonographic Enthesis Index (MASEI). Method This cross-sectional study includes videos of entheses evaluated by ultrasound (US) of 30 patients with SpA diagnosed according to the ASAS criteria and 30 patients with gout established by the presence of monosodium urate crystals. Entheses were evaluated for MASEI in 2 Institutes located in two different countries. Demographic and clinical data were registered. Total MASEI score, MASEI-inflammatory, and MASEI-chronic damage were analyzed. Comparisons between groups were obtained by chi-square test and Student's t-test. An inter-reading US reliability was realized. Results Patients with gout were older and had significantly more comorbidities than those with SpA. The total MASEI score was not significantly different among diseases (p = 0.07). MASEI-inflammatory was significantly more prevalent at the Achilles tendon in SpA, while the proximal patellar tendon was in gout. Power Doppler was higher in SpA compared to gout (p = 0.005). MASEI-chronic damage related to calcification/enthesophytes predominated in gout (p = 0.043), while calcaneal erosions did in SpA (p = 0.008). The inter-reader concordance was excellent (0.93, CI 95% 0.87–0.96, p = 0.001). Conclusions SpA and gout similarly involve entheses according to MASE, however, some inflammatory and chronic lesions differ significantly depending on the underlying disease and tendon scanned.